Dealektika Pemikiran dalam Dialog Antar Umat Beragama: Studi Kasus Forum Persaudaraan Umat Beriman (FPUB) DI. Yogyakarta - Rifa'i, Afif (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2017)
Forum Persaudaraan Umat Beriman (FPUB) is a communication forum among the faithful initiated by interfaith religious scholars who aim to build true peace and brotherhood by placing multicultural spirituality as the foundation of the movement. Based on this, this study answers the problem formulation, as follows: (1) how FPUB effort in building inter-religious dialogue in Yogyakarta? (2) what are the constraining factors in FPUB’s efforts to build interfaith dialogue in Yogyakarta. This study aims to describe the efforts of FPUB in building interreligious dialogue in Yogyakarta and reveal what are the obstacles in the effort of FPUB to build interreligious dialogue in Yogyakarta. The informants in this study consisted of Leaders/People of FPUB initiatives. Data collection methods used were interview, observation and documentation, while data analysis was done with qualitative approach. To achieve this goal, this forum has divisions and coordinators that support various activities, namely (1) Division of religious dialogue: conducting dialogue with visits to various places of worship, hermitage and village hall, dialogue of works and social assistance in the affected areas. 2). Peace Campaign Division: organizes peaceful campaigns through various cultural activities, interfaith prayer, interfaith intercession, humanitarian action and the spread of peaceful action through the media. 3). Media and Information Division: publishes magazine titles to disseminate ideas and interfaith dialogue activities organized by FPUB. The obstacles faced by FPUB in establishing genuine peace and brotherhood are prejudice, both internal and external to religious communities who still prejudice negative and suspicious dialogues among interfaith dialogue. Forum Persaudaraan Umat Beriman (FPUB) merupakan forum komunikasi antar umat beriman yang digagas oleh para agamawan lintas agama yang bertujuan untuk membangun perdamaian dan persaudaraan sejati dengan menempatkan spiritualitas multikultur sebagai fondasi gerakan. Berdasarkan hal ini, maka penelitian ini menjawab rumusan masalah, sebagai berikut: (1) bagaimana upaya FPUB dalam membangun dialog antar agama di Yogyakarta? (2) apa saja faktor penghambat dalam upaya FPUB membangun dialog antar agama di Yogyakarta. Penelitian ini bertujuan untuk mendeskripsikan upaya FPUB dalam membangun dialog antar agama di Yogyakarta dan mengungkapkan apa saja yang menjadi penghambat dalam upaya FPUB membangun dialog antar agama di Yogyakarta. Informan dalam kajian ini terdiri dari pemuka/tokoh pemrakarsa FPUB. Metode pengumpulan data yang digunakan adalah wawancara, observasi dan dokumentasi, sedangkan analisis data dilakukan dengan pendekatan kualitatif. Untuk mencapai tujuan tersebut, forum ini mempunyai divisi dan koordinator yang menunjang berbagai kegiatan, yaitu (1) Divisi dialog agama: menyelenggarakan dialog dengan berkunjung ke berbagai tempat ibadah, padepokan dan balai desa, dialog karya serta bantuan sosial pada daerah yang tertimpa musibah. 2). Divisi Peace Campaign (Kampanye Damai): menyelenggarakan berbagai kampanye damai melalui berbagai aktivitas budaya, doa bersama lintas iman, syawalan antar iman, aksi kemanusian dan penyebaran aksi damai melalui media. 3). Divisi Media dan Informasi: menerbitkan majalah Suluh untuk menyebarkan gagasan dan kegiatan dialog antar iman yang diselenggarakan oleh FPUB. Hambatan yang dihadapi oleh FPUB dalam membangun perdamaian dan persaudaraan sejati adalah adanya prejudice atau prasangka, baik dari internal maupun eksternal umat beragama yang masih menaruh prasangka negatif dan kecurigaan terhadap dialog antaragama.